Using the Ventrogluteal Site for Intramuscular Injection - (:unkn) unknown (My University, 2020)
Intramuscular (IM) injection is one of the most common invasive procedures performed by nurses. Many complications due to unsafe IM injections have been reported in the literature. Most of these complications develop due to injections into the dorsogluteal (DG) site. Recent studies conducted to increase safe injectionapplications have determined that the DG site is the most risky region for IM injections because it is close tosciatic nerves, may have subcutaneous adipose tissue thick enough to prevent access to target muscles, and allows to detect injection site only with imaginary lines. However, the ventrogluteal (VG) site has been reportedas the most reliable region for and suggested as the first choice of IM injections because it is far from sciaticnerves, receives the blood from small branches of arteries, allows detecting injection site by palpating bonestructures, and has subcutaneous adipose tissue thin enough to reach target muscles. Despite the changes inthe literature regarding site selection for IM injections, studies have reported that nurses prefer the DG site asthe first choice for administering IM injections. In addition, studies of the reasons why nurses prefer the DGsite for IM injections have emphasized that they do not have adequate knowledge of VG injections.This studywas conducted to explain the reasons why the IM site should be preferred for administering IM injections toincrease the level of knowledge on the administration of IM injections into the IM site and to raise the use ofthe IM site for administering IM injections.